Respostas
respondido por:
10
d = √(x2 - x1)²+ √(y2 - y1)²
d² = (x2 - x1)² + (y2 - y1)²
3² = (x2 - x1)² + (y2 - y1)²
9 = (0 - a)² + (2 - 1)²
9 = a² + 1
a² = 8
a = √8
a = 2√ 2
Tentei por uma única raiz quadrada para (x2 - x1) + (y2 - y1) mas não consegui
d² = (x2 - x1)² + (y2 - y1)²
3² = (x2 - x1)² + (y2 - y1)²
9 = (0 - a)² + (2 - 1)²
9 = a² + 1
a² = 8
a = √8
a = 2√ 2
Tentei por uma única raiz quadrada para (x2 - x1) + (y2 - y1) mas não consegui
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás